2022
DOI: 10.3389/fimmu.2022.857014
|View full text |Cite
|
Sign up to set email alerts
|

The Shared Mechanism and Candidate Drugs of Multiple Sclerosis and Sjögren’s Syndrome Analyzed by Bioinformatics Based on GWAS and Transcriptome Data

Abstract: ObjectiveThis study aimed to explore the shared mechanism and candidate drugs of multiple sclerosis (MS) and Sjögren’s syndrome (SS).MethodsMS- and SS-related susceptibility genes and differentially expressed genes (DEGs) were identified by bioinformatics analysis based on genome-wide association studies (GWAS) and transcriptome data from GWAS catalog and Gene Expression Omnibus (GEO) database. Pathway enrichment, Gene Ontology (GO) analysis, and protein–protein interaction analysis for susceptibility genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Our MR analysis identi ed a positive correlation between IL-10RB and SS risk. Given the reported close relationship between JAK-STAT and SS development (49,50), the potential role of abnormal IL-10RB expression and mediation of JAK-STAT pathway activation in SS pathogenesis merits in-depth exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Our MR analysis identi ed a positive correlation between IL-10RB and SS risk. Given the reported close relationship between JAK-STAT and SS development (49,50), the potential role of abnormal IL-10RB expression and mediation of JAK-STAT pathway activation in SS pathogenesis merits in-depth exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown a significant reduction in arthritis severity and migration of Th17 cells to joints following the use of monoclonal antibodies against CCR6 [ 55 ]. HLA-DPA1 was identified as a common drug target for both Sjogren's syndrome and multiple sclerosis in a previous study [ 56 ], while another study more directly by weighted gene co-expression network (WGCNA) and linkage map (CMap) of illustrating HLA-DPA1 as a drug target for RA [ 57 ]. HLA-DRB1 is a recognised susceptibility-associated gene [ 58 ] with the strongest association with autoantibody-positive RA [ 59 , 60 ] and the HLA-DRB1*13 allele was found to confer strong protection against RA [ 61 ], which is consistent with the results of this study.IFNGR2 is a known causally associated gene for RA [ 62 ] and has also been identified as a potential target for the autoimmune disease, psoriasis [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is interesting to note that despite sicca symptoms being rare at the beginning, almost all of our CNS patients had serological and histological evidence of an inflammatory affection of salivary glands typical of pSS. Therefore, at least an accompanying pSS is to be assumed, and data from genome-wide association studies suggest at least a genetic overlap ( 32 ). Given that the diagnosis of MS can only be made when there is no better explanation ( 10 ), there were also hints calling even the diagnosis of MS into question.…”
Section: Discussionmentioning
confidence: 99%